Genetic dissociation of three antigenic genes in Plasmodium ovale curtisi and Plasmodium ovale wallikeri - Saralamba, N; Nosten, F; Sutherland, C; Arez, A; Snounou, G; White, N; Day, N; Dondorp, A; Imwong, M (Public Library of Science, 2019)
Plasmodium ovale curtisi and Plasmodium ovale wallikeri are two sympatric human malaria species prevalent in Africa, Asia and Oceania. The reported prevalence of both P. ovale spp. was relatively low compared to other malaria species, but more sensitive molecular detection techniques have shown that asymptomatic low-density infections are more common than previously thought. Whole genome sequencing of both P. ovale spp. revealed genetic dissociation between P. ovale curtisi and P. ovale wallikeri suggesting a species barrier. In this study we further evaluate such a barrier by assessing polymorphisms in the genes of three vaccine candidate surface protein: circumsporozoite protein/ thrombospondin-related anonymous-related protein (ctrp), circumsporozoite surface protein (csp) and merozoite surface protein 1 (msp1). The complete coding sequence of ctrp and csp, and a partial fragment of msp1 were isolated from 25 P. ovale isolates and compared to previously reported reference sequences. A low level of nucleotide diversity (Pi = 0.02–0.10) was observed in all three genes. Various sizes of tandem repeats were observed in all ctrp, csp and msp1 genes. Both tandem repeat unit and nucleotide polymorphism in all three genes exhibited clear dimorphism between P. ovale curtisi and P. ovale wallikeri, supporting evidence of non-recombination between these two species.